Challenge and opportunity for OECD industries (Paris, 1988)
This book introduce about OECD trade in manuafactures the NICs. Industrial strategies of the NICs. The Nic "challenge" and responses by OECD countries. Main finding and policy implications.
Keywords: Các nước đang phát triển,Developing countries; Điều kiện kinh tế,Economic conditions